2020
DOI: 10.1002/cpa.21948
|View full text |Cite
|
Sign up to set email alerts
|

Transition Threshold for the 3D Couette Flow in Sobolev Space

Abstract: In this paper, we study the transition threshold of the 3D Couette flow in Sobolev space at high Reynolds number Re. It was proved that if the initial velocity v 0 satisfies kv 0 .y; 0; 0/k H 2 c 0 Re 1 for some c 0 > 0 independent of Re, then the solution of the 3D Navier-Stokes equations is global in time and does not transition away from the Couette flow. This result confirms the transition threshold conjecture proposed by Trefethen et al. in 1993. Moreover, we prove that the long-time dynamics of the solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
(89 reference statements)
2
10
0
Order By: Relevance
“…The main results. The aim of this paper is to rigorously study the stability properties of the Couette flow for the 3D linearized isentropic compressible Navier-Stokes equations on T × R × T. We confirm the enhanced dissipation and the lift-up phenomena which have been deeply studied for the 3D incompressible fluids [6,64].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The main results. The aim of this paper is to rigorously study the stability properties of the Couette flow for the 3D linearized isentropic compressible Navier-Stokes equations on T × R × T. We confirm the enhanced dissipation and the lift-up phenomena which have been deeply studied for the 3D incompressible fluids [6,64].…”
Section: Introductionsupporting
confidence: 56%
“…It is a challenging task to study the transition threshold problem of the Couette flow in the three dimensional finite channel T×[−1, 1]×T. Despite the boundary layer effect, it was shown by Chen, Wei and the second author in a very rencent work [18] that the threshold is still not larger than 1 (just as in the case without boundary [64]), and thus the conjecture proposed by Trefethen et al [63] was confirmed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We now explore scaling of H ∇ µ at higher Reynolds numbers for plane Couette flow, which is known to be linearly stable for Re → ∞ (Romanov 1973). The scaling of permissible perturbation amplitude versus Reynolds number in the asymptotic limit Re → ∞ is also widely studied (Kreiss et al 1994;Chapman 2002;Bedrossian et al 2015Bedrossian et al , 2019Wei & Zhang 2020). Here we analyze this behavior by investigating computing results at Re = 15000, 25000, 35000, 100000, 280000, with associated increased wall-normal resolution including N y = 60, 80, 100, 120, 140 wall-normal grid points, respectively.…”
Section: Reynolds Number Dependencementioning
confidence: 99%
“…• Three-dimensional Couette flow in T R T : If X is taken as a Sobolev space, then D 1 gives stability ( [3][4][5]40]). Also see the very recent paper [15] for threedimensional Couette flow in a finite channel.…”
Section: Introductionmentioning
confidence: 99%